Peculiarities of the spatial organization of the ecological niche of Vallonia pulchella (Muller, 1774) on the pedozems of the Nikopol manganese ore basin - A. K. Umerova (Agrology, 2020)
As a result of the experiment, the ecological niche of the micromollusc Vallonia pulchella on artificial soil-like structures was investigated, with use of the edaphic and phytoindication indices. The study was conducted in June 2019 at a research path within the Nikopol manganese ore basin (on pedozem). The experimental polygon consisted of 105 samples located within 7 transects (15 samples each). The distance between the rows in the polygon is 3 m. The average density of the investigation object is 1.18 specimens/m2. It is shown that the spatial organization of the micromollusc is structured under the influence of edaphic and phytoindication indices. The edaphic and plant factors can be considered as determinants of the ecological space of V. pulchella, which is accomplished within the framework of the theory of ecological niche. It is established that the average soil hardness increases with depth down the profile. The influence of the hardness of deep soil layers on the distribution of mollusсs, which occur mainly on the surface, can be considered as a result of indirect influence through the structure of vegetation. Micromolluscs give an advantage to the places with a dominance of aggregates, which belong to the category of agronomically valuable (size from 1‒2 to 3‒5 mm). Small (less than 0.25‒0.5‒1.0 mm) and large aggregates (more than 10 mm) negatively affect the number of V. pulchella. Phytoindication scales act as valuable indicators to describe the properties of the ecological niche of the investigated object. The micromolluscs V. pulchella give an advantage to the areas with high levels of carbonic salts, as well as with a low content of free nitrogen in the soil. The indicators of ombroclimate and termal conditions contribute to the increase in the number of molluscs. Further research will be directed to study the impact of vegetation on the ecological niche of the micromollusc Vallonia pulchella (Muller, 1774) with application of geostatic analysis